Analisis Kedudukan Konsumen yang Dirugikan Akibat Penggunaan Obat Disfungsi Ereksi yang Tidak Terdaftar di Badan Pengawasan Obat dan Makanan (BPOM) dalam Hukum Perlindungan Konsumen - Rifki, Muhammad (LPPM Universitas Ekasakti Padang, 2024)
This writing analyzes the position of consumers who are harmed due to the use of illegal erectile dysfunction drugs in consumer protection law, as well as the accountability of business actors towards consumers harmed by the use of illegal erectile dysfunction drugs.. This writing is composed using a normative juridical research method (a normative doctrinal approach) that essentially examines the internal aspects of positive law. In order to protect consumers who become victims of the actions of illegal strong drug traders, the Government, through the Consumer Protection Act, provides legal protection in the form of both preventive and repressive legal protection. Preventive legal protection is protection provided to consumers with the aim of preventing disputes or issues. As for repressive protection efforts that can be taken in connection with the practice of production and trade of illegal strong drugs in Indonesia, it involves optimizing litigation and non-litigation avenues. Repressive legal protection aims to resolve disputes or conflicts that have already occurred. Provisions regarding the resolution of consumer protection disputes through litigation are stated in Pasal 45 of the Undang-Undang Perlindungan Konsumen, while for the resolution of non-litigation disputes, BAB XI of the Undang-Undang Perlindungan Konsumen states that it can be done through the Consumer Dispute Resolution Board or Badan Penyelesaian Sengketa Konsumen (BPSK).